The Experience of Career for People Who Have Moved into Supervisory and Management Roles in a Social Service Organization - Stevens, Alison M.; Amundson, Norman (Canadian Journal of Counselling and Psychotherapy, 2008)
Funding cuts and organizational restructuring are among the factors that contribute to making the social service sector a stressful environment in which to work. This qualitative study explores how the values, beliefs, and motivation of supervisors and managers in the social service sector change over time and how they make meaning in their work life. Participants have specific expectations of what they need from their work environment, and they want to affect their environment through using their particular knowledge and skills. Mitigating factors that enable success include having a supportive agency, seeing that one’s work has an impact on the environment, and having a voice.